Role of Vitamin E on Indomethacin induced low pH of Seminal Fluid in Long Evans Rats - Alam, Md Jahangir; Naushaba, Humaira; Paul, Uttam Kumar; Begum, Tahmina; Shahriah, Sunjida; Ahmed, Md Shameem; Hossain, Md Moazzem (Bangladesh Journal of Anatomy, 2010)
Context: Indomethacin is the most commonly and widely used nonsteroidal antinflammatory analgesic and antipyretic drug. Though it is effective drug in various diseases, indomethacin causes inhibition of spermatogenesis by lowering the pH of seminal fluid leading to infertility. On the other hand, vitamin E enhances spermatogenesis by increasing pH of the seminal fluid. Therefore, the present study was designed to observe the protective role of vitamin E on indomethacin induced low pH of seminal fluid in testicular damage. Objective: To observe the effects of vitamin E on indomethacin induced low pH of seminal fluid in testicular damage in Long Evans rats. Study design: An experimental study. Place and period of study: The study was carried out in the Department of Anatomy, Sir Salimullah Medical College, Dhaka in the period of August, 2005 to June, 2006. Materials and methods: Eightyfour mature Long Evans male rats were divided into four groups (I, II, III and IV). The rats of group I, II and III were treated with indomethacin at different doses and duration. Group IV rats were treated with indomethacin plus vitamin E at different doses for 49 days. The pH of seminal fluid were measured biochemically. Results: There was significant reduction (P<0.001) of pH of seminal fluid when the rats were treated with indomethacin at low (2 mg/kg body weight/day) and high (10 mg/kg body weight/day) doses for 7, 14 and 42 days, respectively. On the other hand, rats treated with indomethacin plus vitamin E for 49 days showed increase in pH of seminal fluid compared to other groups (P<0.001). Conclusion: It can be concluded from the study that vitamin E has potential role in the prevention of the antispermatogenic effects of indomethacin by increasing the pH of seminal fluid. Key words: seminal fluid; indomethacin; vitamin E DOI: 10.3329/bja.v8i1.6103 Bangladesh Journal of Anatomy January 2010, Vol. 8 No. 1 pp. 13-15